Sistem Pembayaran SPP pada SMK Berbasis Web Menggunakan Metode Waterfall - Agung Alfisyakhrin; Ismasari Nawangsih; Ikhsan Romli (STMIK Budi Darma, 2023)
The development of a web-based tuition fee payment system at SMK Global Mulia is relevant for enhancing administrative efficiency and accuracy. The Waterfall method is employed in this development for a structured approach. SMK Global Mulia Vocational High School faces challenges in tuition fee administration. Manual methods are prone to errors and time-consuming. To address these issues, technology is leveraged by developing a web-based Tuition Fee Payment System. The Waterfall method is used for system analysis, design, implementation, testing, and maintenance. This research focuses on implementing a web-based Tuition Fee Payment Information System using the Waterfall method at SMK Global Mulia. The expected outcome is a positive contribution to similar system development in other educational institutions and resolving tuition fee administration issues at SMK Global Mulia. In this development, the system utilizes the Waterfall method with steps including analysis, design, implementation, testing, and maintenance. The system facilitates the finance department in student payment input and processing. The implementation of the Tuition Fee Payment Information System at SMK Global Mulia demonstrates effectiveness and efficiency in the payment process and student data retrieval. This reduces complexity in generating daily and periodical summaries, while expediting services to students